2010
DOI: 10.5251/ajsir.2010.1.2.279.292
|View full text |Cite
|
Sign up to set email alerts
|

The influence of lithology and depth on acoustic velocities in South-east

Abstract: In this paper, composite well log (gamma ray, sonic and density) was used to identify thin layers of different lithologies and the lithologic boundaries at various depths by the signature records of the logs, and checkshot data were used to check and/or validate the integrated time and sonic derived velocities. The results show that acoustic velocities are very much affected by different lithologic properties and depth; porosity decreases more in shale than sandstone and velocity increases more in shale than s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The empirical formula method is the most common approach to first estimate the shear wave velocity by constructing a linear relationship between logging parameters and Vs (Castagna et al, 1985;Han et al, 1986;Dvorkin, 2008;Parvizi et al, 2015). However, the empirical relationship is highly lithology-and region-specific (Tamunobereton-Ari et al, 2010). In carbonate formation, which has a complex pore structure and strong heterogeneity, the variation of shear wave velocity in carbonate is the result of an interaction between lithofacies, diagenetic process, and porosity (Rafavich et al, 1984;Anselmetti and Eberli, 1993;Tamunobereton-Ari et al, 2010;Qabany et al, 2011;Wang et al, 2011;Kittridge, 2015;Garia et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The empirical formula method is the most common approach to first estimate the shear wave velocity by constructing a linear relationship between logging parameters and Vs (Castagna et al, 1985;Han et al, 1986;Dvorkin, 2008;Parvizi et al, 2015). However, the empirical relationship is highly lithology-and region-specific (Tamunobereton-Ari et al, 2010). In carbonate formation, which has a complex pore structure and strong heterogeneity, the variation of shear wave velocity in carbonate is the result of an interaction between lithofacies, diagenetic process, and porosity (Rafavich et al, 1984;Anselmetti and Eberli, 1993;Tamunobereton-Ari et al, 2010;Qabany et al, 2011;Wang et al, 2011;Kittridge, 2015;Garia et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the empirical relationship is highly lithology-and region-specific (Tamunobereton-Ari et al, 2010). In carbonate formation, which has a complex pore structure and strong heterogeneity, the variation of shear wave velocity in carbonate is the result of an interaction between lithofacies, diagenetic process, and porosity (Rafavich et al, 1984;Anselmetti and Eberli, 1993;Tamunobereton-Ari et al, 2010;Qabany et al, 2011;Wang et al, 2011;Kittridge, 2015;Garia et al, 2019). Thus, simple linear approximation is insufficient for accurately estimating the Vs The rock physics modeling technique for carbonate has being extensively studied by considering different mineral types, pore structures, and fluid conditions, and the studies have shown promising results (Xu and Payne, 2009;Sun et al, 2012;Zhang et al, 2013;Azadpour et al, 2020;Seifi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of using shear velocity is ranging from seismic exploration, calculation of petrophysical properties and evaluation of the well stability. Sometimes not all logs are available, for example the dipole shear sonic imager (DSI) (Rezaee et al 2006, Amunobereton-ari et al 2010). The DSI have both monopole and dipole sonic acquisition abilities for the dependable acoustic measurement of compressional, shear, and Stoneley slowness's.…”
Section: Introductionmentioning
confidence: 99%
“…Velocity is one of the most important petrophysical parameters used in oilfield optimization or other geophysical surveys to easily determine and predict horizons, faults, facies, unconformities, stratigraphic boundaries, geologic structures, fluid contents etc. (Tamunobereton-ari et al, 2010).…”
Section: Introductionmentioning
confidence: 99%